Profil Kesadaran Metakognitif Mahasiswa Baru Generasi Z Di Provinsi Riau Sebagai Basis Penguatan Pendidikan Karakter Di Era Digital - Yeyendra .; Ibnu Hajar; Lizawati . (CV. ITTC INDONESIA, 2026)
Metacognitive awareness is a key competency in 21st-century learning that plays a crucial role in strengthening character education, particularly for Generation Z students who grew up in a digital ecosystem. This study aims to describe the metacognitive awareness profile of new Generation Z students in Riau Province and identify metacognitive aspects that need to be strengthened as a basis for developing character education in higher education. The study used a mixed methods approach with a descriptive quantitative design as the primary method. Data were collected through a metacognitive awareness questionnaire based on the Metacognitive Awareness Inventory (MAI) that included eight sub-variables: declarative knowledge, procedural knowledge, conditional knowledge, planning, information management strategies, monitoring, debugging strategies, and evaluation. The study respondents were 420 new students from four universities in Riau Province. The results showed that the metacognitive awareness profile of new Generation Z students was in the moderate category, with a tendency for higher scores in the metacognitive knowledge aspect compared to metacognitive regulation. The sub-variables of declarative knowledge and information management strategies obtained the highest scores, while monitoring and evaluation showed the lowest scores. These findings indicate the need to strengthen metacognitive regulation as a basis for integrating character education in the digital era.